(untitled) (Research, Society and Development, 2024)
Objective: To investigate and discuss the risks associated with the use of the drug in order to clarify the possible damage to health. Methods: Through an integrative review, using the guiding question “What are the main adverse effects and impacts of using zolpidem?”. The search was carried out in the main databases: Latin American and Caribbean Health Sciences Literature (LILACS), Medical Literature and Retrieval System onLine (MEDLINE/PubMed®), Periódicos CAPES and Scientific Electronic Library Online (Scielo). MESH (Medical Subject Headings) and DeCs (Health Sciences Descriptors) were used as descriptors in the search strategy. The search strategy followed the criteria of the Boolean operator “AND”, which combines terms. The terms used were zolpidem “AND” adverse effects AND overdose, during the month of September 2024. Results: Zolpidem is a drug of paramount importance for the treatment of cases of insomnia, and long-term medical therapy should be monitored to assess efficacy, the emergence of adverse effects and the onset or worsening of comorbid conditions. Conclusion: Strict prescription control and continuous evaluation of its impact on patients’ physical and mental health are essential to avoid abuse and serious complications.